Pengaruh Kedisiplinan, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Flora Wisata Santerra De Laponte) - Yuzril Hanafi Aryanata; Nurhidayah Nurhidayah; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study was conducted to determine the effect of discipline, work motivation and work environment on employee performance (Case Study on Flora Wisata Santerra De Laponte). This study uses a quantitative approach. Saturated sample is a sampling technique if the entire population is used as a sample, the total sample in this study is 70 people. To solve the problem in this research, using validity test, reliability test, normality test, path analysis test, hypothesis test which includes direct effect with t test, indirect effect with Sobel test, and coefficient of determination test R2. This study uses hypothesis testing with the help of SPSS 16.0. The results of this study are the independent variables Discipline, Work Motivation, Work Environment have a significant effect together on the dependent variable of Employee Performance. Discipline variables have a significant effect on employee performance, discipline variables significantly affect employee performance and work environment variables significantly affect employee performance Flora Wisata Santerra De Laponte. Keywords : Employee performance, discipline, work motivation, work environment